Tree characterization to improve thermal comfort, in the city of Santiago de Guayaquil - Iturralde, Orlando Adolfo Hermida; Cañarte, Carlos Alberto Nieto; Carpio, Byron Andres Burgos; Yépez, Carlos Vinicio Sanabria (Seven Editora, 2023)
The reduction of temperature under trees due to evapotranspiration and canopy covering, widely studied according to its species and valued by indexes, has not been studied within Guayaquil, a city that in addition to being characterized by its high temperatures during the year, presents manifestations of the Urban Heat Island (ICU) phenomenon. The present study analyzes the direct influence on the temperature reduction of 19 tree species found within the urban area through the equivalent physiological temperature index (PET) obtained from the Rayman Pro model and details the predominant landscape characteristics in the city exemplified in 2 residential areas, to discern the adjustment of 5 efficient species to mitigate the ICU effect. The results show the introduced species as the most optimal, but of potential conflicts with the urban infrastructure already conceived, it was not possible to determine the location of moderately efficient species without following a specific pattern in both study areas. DOI:https://doi.org/10.56238/alookdevelopv1-060